Censorship. A Philological (and Rhetorical) Viewpoint - Salazar, Philippe-Joseph (Javnost-The Public, 2004)
The word “censorship” is philologically rooted in a glossary of key notions that span across the spectrum of the paradigm of authority. Based on analyses by Émile Benveniste, from his Vocabulaire des institutions indo-européennes, this essay aims at bringing out the censorial denotations of “authority,” “war,” “award,” “direction,” as well as the embedded censorial dimension of, for instance, the rhetorical presidency. It closes on a reflexion concerning the censorial drift, within democracy, from demos to laos.